From action to ethics: A process-relational approach to prosocial development - Carpendale, Jeremy I. M.; Wallbridge, Beau (Frontiers in Psychology, 2023)
Explaining how children first become active prosocial and then later moral agents requires, we argue, beginning with action and interaction with others. We take a process-relational perspective and draw on developmental systems theory in arguing that infants cannot be born knowing about prosociality or morality or anything else. Instead, they are born with emerging abilities to act and react. Their biological embodiment links them to their environment and creates the social environment in which they develop. A clear distinction between biological and social levels cannot be made in the context of ongoing development because they are thoroughly interwoven in a bidirectional system in which they mutually create each other. We focus on infants’ emerging ability to interact and develop within a human developmental system, and prosociality and morality emerge at the level of interaction. Caring is a constitutive aspect of the forms of experience in which infants are embedded in the process of becoming persons. Infants are immersed in a world of mutual responsiveness within caring relationships that are infused with concern, interest, and enjoyment. In such a developmental system, infants become persons when they are treated as persons.